2013
DOI: 10.1177/0269881113495722
|View full text |Cite
|
Sign up to set email alerts
|

The influence of test experience and NK1 receptor antagonists on the performance of NK1R-/- and wild type mice in the 5-Choice Serial Reaction-Time Task

Abstract: Genetically-altered mice, lacking functional NK1 receptors (NK1R-/-), express abnormal behaviours that are prominent in Attention Deficit Hyperactivity Disorder: namely, inattentiveness and impulsivity (indicated by their greater % omissions and premature responses in the 5-Choice Serial ReactionTime Task (5-CSRTT) and locomotor hyperactivity. We investigated how behaviour in the 5-CSRTT is affected by repeated testing and whether the abnormalities expressed by NK1R-/-mice are mimicked by treating wild type mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Our previous experiments have confirmed that repeated experience of the VITI can influence behaviour in this test (see Weir et al ., 2014 ). For this reason, the response to guanfacine in this study was compared with NI-2, which was the uninjected control embedded within the series of drug treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous experiments have confirmed that repeated experience of the VITI can influence behaviour in this test (see Weir et al ., 2014 ). For this reason, the response to guanfacine in this study was compared with NI-2, which was the uninjected control embedded within the series of drug treatments.…”
Section: Resultsmentioning
confidence: 99%
“…These drug doses were chosen because they modify relevant aspects of behaviour in mice: for example, working memory in a T-maze (Franowicz et al ., 2002 ) and locomotor activity (Archer and Fredriksson, 2003 ). NI-2 (baseline behaviour of uninjected mice) was embedded within the sequence of vehicle/drug treatments to control for any systematic changes in behaviour arising from rehearsal of the test (see Weir et al ., 2014 ). The vehicle/drug/NI-2 sessions were counterbalanced across subjects, using a pseudo William’s Latin square, such that each mouse received each treatment, or NI-2 session, once only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not carried out a randomised, head-to-head comparison of the two genotypes in the 5CSRTT and 5C-CPT. However, our findings so far suggest that the longer LITI, used in the 5CSRTT, is more effective than the protocol in this 5C-CPT for discerning a higher proportion of omission errors in NK1R–/– mice than in wild types (Porter et al, 2015a; Weir et al, 2014; Yan et al, 2011; see also Porter et al, 2016). …”
Section: Discussionmentioning
confidence: 71%
“…These mutant mice also display impaired cognitive performance and response control in the 5-Choice Serial Reaction Time Task (5CSRTT). Typically, they score more % premature responses (an index of impulsivity) and % omissions (an index of inattentiveness) than wild types (Dudley et al, 2013; Porter 2015a, 2015b; Yan et al, 2011), especially when tested for the first time (Weir et al, 2014). It is striking that these three behavioural abnormalities meet the diagnostic criteria for ADHD in humans.…”
Section: Introductionmentioning
confidence: 99%